Extended variable-time-step Adams–Bashforth–Moulton method for strongly coupled fluid–structure interaction simulation. (1st January 2021) - Wang, Dongxu; Dong, Sheng; Ning, Meng; Incecik, Atilla
Abstract: An extended variable-time-step Adams–Bashforth–Moulton (ABM) method is presented for obtaining the solution of six-degrees-of-freedom (6DoF) rigid body motion. This second-order method involves the use of one predictor and several correctors, thus requiring an iteration process during each time step. Aitken's dynamic under-relaxation (ADUR) scheme is used to reduce the time to convergence. The initial value of the under-relaxation factor at each time step is evaluated from the values of the two previous time steps, the predictor, and the first corrector. Cooperating with the incompressible two-phase flow solver included in OpenFOAM®, the present method is capable of simulating fluid–structure interaction (FSI) problems, in which strong coupling is ensured through the outer loop of the PIMPLE algorithm. Various interface capture schemes as well as mesh motion schemes are considered. Several two- and three-dimensional cases of multi-DoF are simulated, and the recommended iteration stop condition is summarised. Finally, the method is employed to reproduce an experiment that investigates the interaction between a dam-break flow and a floating box. Satisfactory overall agreement between the numerical and experimental results is observed, which demonstrates that the method is suitable for simulating FSI problems in ocean engineering. Highlights: A strongly coupled method for simulating fluid–structure interaction is proposed. A novel approach is derived to evaluate the initial under-relaxation factor of Aitken's dynamic under-relaxation. An experiment is set up to investigate interaction between dam-break flow and a floating structure.